Interpreting Puccini’s Suor Angelica: An application of the semiotics of temporality - Davis, Andrew (Interdisciplinary Studies in Musicology, 2018)
This article summarizes recent discussions in the secondary literature of the semiotics of temporality, understood not as time per se but as the “time signified” by the signs in any semiotic system. Drawing especially on theories of the late Raymond Monelle and noting parallels with Monelle in work of, for example, Abbate, Daverio, Kinderman, Hatten, and Berger, the article posits that states of “temporality” in music can correlate with the syntactic signification of linear, teleological motion through time, whereas states of “atemporality” can correlate with syntactic signification of suppressed linear motion through time. As one of the distinguishing semantic characteristics of post Classical music, the signification of extended moments of atemporality is understood as a central expressive issue in the structure of Puccini’s Suor Angelica (from the II trittico of 1918), an opera that divides approximately into two halves: an atemporal half focused on portraying the Roman Catholic church, and a temporal half focused on exploring the character of Angelica, where both halves also include “tropes of temporality” cued by juxtapositions of temporal and atemporal signifiers. That the church in Suor Angelica is elevated to the position of the drama’s primary antagonist is asserted as one of the ways with which the piece engages with the aesthetics of “realism”, an aesthetic that, in turn, informs an interpretation of the opera’s ending, which includes a deus ex machina in the form of an appearance of the Virgin Mary and an apparition of Angelica’s dead son.